2017
DOI: 10.1007/s40136-017-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic (IT) Therapies for Menière’s Disease: Some Consensus Among the Confusion

Abstract: Purpose of Review Aminoglycosides and corticosteroids are commonly used to treat Menière's disease. Intratympanic (IT) administration of these medications allows high inner ear concentrations without significant adverse systemic effects. As a direct result, IT therapy has grown in popularity. Recent studies have compared patient outcomes between IT aminoglycosides and corticosteroids. This review summarizes these findings. Recent Findings Trials comparing IT corticosteroids to IT placebo or oral therapy have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 102 publications
0
12
0
3
Order By: Relevance
“…Lifestyle adjustments like rest, avoiding sudden position changes, and hydration have been recommended. 84,86 During acute vertigo attacks, patients can benefit from vestibular suppressants. The most frequently used drugs are benzodiazepines (diazepam, lorazepam, clonazepam), H1 antihistamines receptor (meclizine, diphenhydrinate, promethazine), antidopaminergic agents (metoclopramide), anticholinergics (diphenhydramine), and antiemetic 5-HT 3 antagonists (ondansetron).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle adjustments like rest, avoiding sudden position changes, and hydration have been recommended. 84,86 During acute vertigo attacks, patients can benefit from vestibular suppressants. The most frequently used drugs are benzodiazepines (diazepam, lorazepam, clonazepam), H1 antihistamines receptor (meclizine, diphenhydrinate, promethazine), antidopaminergic agents (metoclopramide), anticholinergics (diphenhydramine), and antiemetic 5-HT 3 antagonists (ondansetron).…”
Section: Treatmentmentioning
confidence: 99%
“…[93][94][95] Finally, in case of failure of conservative therapies, intratympanic gentamicin could be proposed to induce a partial chemical labyrinthectomy. 86,[96][97][98][99][100][101][102][103] Several reviews have evaluated the effectiveness of intratympanic therapies, supporting their use in MD. 104,105 -Surgery: This must be considered with caution, since MD may become bilateral after surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…When applied systemically, the phosphate is cleaved by phosphatases in the liver, by which time the drug is diluted to a degree that the dexamethasone remains in solution. Intratympanically-administered dexamethasone-phosphate is used clinically to treat Meniere’s disease and idiopathic sudden sensorineural hearing loss [Schoo et al, 2017; Plontke et al, 2009]. It is usually injected at concentrations of 4 – 12 mg/mL [review and meta-analysis by Liebau et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…First-line treatment includes dietary restrictions for salt, caffeine, and alcohol associated to drugs both for acute attacks (dimenhydrinate, benzodiazepines) 12 , and as prophylactic therapy (betahistine, β-blockers, diuretics) 13 . When first-line treatment does not offer satisfactory symptom control, intratympanic (IT) administration of gentamicin or corticosteroids can be performed 14 ; however, many studies showed that IT gentamicin may expose the patients to a risk of hearing loss, depending on dosage and intervals between administrations 15 . Labyrinthectomy or other surgical procedures can be suggested for intractable MD 16 .…”
Section: Introductionmentioning
confidence: 99%